Disease features of equine coronavirus and enteric salmonellosis are similar in horses. (10th January 2019) - Manship, Arlie J.; Blikslager, Anthony T.; Elfenbein, Johanna R.
Abstract : Background: Equine coronavirus (ECoV) is an emerging pathogen associated with fever and enteric disease in adult horses. Clinical features of ECoV infection have been described, but no study has compared these features to those of Salmonella infections. Objectives: Compare the clinical features of ECoV infection with enteric salmonellosis and establish a disease signature to increase clinical suspicion of ECoV infection in adult horses. Animals: Forty‐three horses >1 year of age with results of CBC, serum biochemistry, and fecal diagnostic testing for ECoV and Salmonella spp . Methods: Medical records of horses presented to the North Carolina State University Equine and Farm Animal Veterinary Center (2003‐016) were retrospectively reviewed. Horses were divided into 3 groups based on fecal diagnostic test results: ECoV‐positive, Salmonella‐ positive, or unknown diagnosis (UNK). Time of year presented, clinical signs, CBC, and serum biochemistry test results were recorded. Data were analyzed by 1‐way analysis of variance, Kruskal‐Wallis test, or Fisher's exact test with significance set at P < .05. Results: Most common presenting complaints were fever and colic and were similar across groups. Horses with ECoV had significantly decreased neutrophil counts when compared to those with no diagnosis but were not different from horses with Salmonella . Horses with Salmonella had significantly lower mean leukocyte counts compared to those with UNK. No significant differences were found among groups for any other examined variable. Conclusions and Clinical Importance: Equine coronavirus and Salmonella infections share clinical features, suggesting both diseases should be differential diagnoses for horses with fever and enteric clinical signs.